URGENSI PENINGKATAN KOMPOTENSI DAN PROFESIONAL DOSEN - Muhammad Sidik (LP2M-Institut Agama Islam Abdullah Said Batam, 2023)
Educational institutions are the institutions most responsible for realizing the intelligence of the nation's children. And the spearhead of educational institutions to make this happen are the teachers, both teachers and lecturers. On that basis, lecturers who are assigned as educators on campus are required to carry out their duties as well as possible. But what can you do, even though the government and lecturers on various campuses have realized their tasks, negative justifications are still quite often addressed to the world of education, including campuses. So to improve the image of the world of education and the world of campus, the lecturers on campus have the responsibility to increase their potential and professionalism at work. Some of the competencies that are required to be mastered by lecturers are pedagogic competence, personal competence, social competence and professional competence. To improve some of these competencies, there are several factors that must be done. Among them are updating their level of education, participating in scientific and professional training, adding experience, facilitating the availability of teaching and learning process facilities for lecturers, and the nominal amount of salary and allowances received by lecturers.